Motion Capture Technique with Enhancement Filters for Humanoid Model Movement Animation - Habibillah, Ahmad Yasin; Prahara, Adhi; Murinto, Murinto (Mobile and Forensics, 2023)
The definition of 3D animation is a representation of objects that are made into animation using characters or objects to look more alive and real. Making 3D animation itself requires a long process and a large amount of funding. This is because most 3D animated films still use key-framing technology which causes the process to make an animation to take a lot of steps. In this research, a motion capture technique with an enhancement filter is proposed to make humanoid movement animation using Kinect 2.0. The method consists of several steps such as recording every skeleton joint of human movements using a Kinect sensor, filtering the movements to minimize the shakiness and jitter from Kinect data, mapping skeleton data to the bones of a rigged humanoid model, and recording each movement to make animation. The final result is in the form of a 3D animation of modern dance movements. The method is tested by measuring the similarity between the 3D humanoid model and the user movement. From the 10 animations of modern dance generated by the method and performed by the user, a questionnaire to measure the MRI and MSE value is distributed and the result achieves 4.27 on a scale of 5 for the averaged MRI score and 0.0539 for the MSE score. The MSE value is less than 5% which means the system is categorized as acceptable.